Tres diplomas del cardenal Luna relativos a León. Estudio diplomático - Domínguez Sánchez, Santiago (Estudios humanísticos. Geografía, historia y arte, 2001)
In this paper are analyzed, using the traditional method of the diplomatic science, three documents of Peter Martinez de Luna, cardinal of Saint Mary in Cosmedin, legate in Spain (1378-1390) of the Pope Clement VII of Avignon -and, in the futuro, Pope (1394-1423)-. The refered documents come from the monastic archives of Saint Mary of Carbajal and Saint Isidore of Leon.